Effects of Brachiaria decumbens stapf in short- and long-term feeding on in vitro rumen fermentation and growth performance in sheep - Jaapar, Mimi Syazwani (2021)
Brachiaria species have been planted on more than 80% of improved farming pastures with Brachiaria decumbens as the most favoured species. It is important because of its high productivity under intensive use, and its tolerance of low fertility soil. However, the presence of steroidal saponins in B. decumbens which had become a limiting factor led to the outbreaks of photosensitivity in ruminants. This current study focused on the effects of B. decumbens in short and long-term feeding on In Vitro gas production, rumen fermentation, nutrient digestibility and growth performance in sheep. A total of 30 (6-month-old) male Dorper cross sheep were divided randomly into 3 treatment groups with 10 sheep per treatment. This study was conducted in 2 phases which is the shortterm (7 days) and long-term (90 days) stages excluding the 2 weeks adaptation period. Treatment 1 (control) sheep were fed with Pennisetum purpureum and concentrates as the basal diet, whereas Treatment 2 and 3 sheep were fed with low (10%) and high (60%)) levels of B. decumbens respectively according to 3% kg/feed per body weight. The digestibility trial was done at day 7 during the shortterm and at day 90 during the long-term. The amount of feed offered and refusals were recorded daily while body weight gain and body measurement were recorded weekly to determine the feed efficiency. The In Vitro gas production showed no significant changes in net gas production and gas production kinetics during the 48 hours on incubation. However, the gas production significantly decreased as the level of B. decumbens increases, with T3 diet demonstrated poorest gas production. The concentration of ammonia and pH showed no significant difference among treatments but decreasing as B. decumbens level increases. The same goes with all individual VFA except for acetic acid and total VFA (p<0.05) The sheep digestibility of organic matter, neutral detergent fiber, and crude protein except dry matter showed no significant differences (p>0.05) during the short-term, while DM, CP, NDF and acid detergent fiber decreased significantly (p<0.05) during the long-term. For the growth performance and feed intake, there were also no significant differences during the short-term. Meanwhile, there were significant differences in total weight gained each week, average daily gain (ADG), total feed intake and daily feed intake recorded daily during the long-term. T3 sheep fed with the highest concentration of B. decumbens exhibited the worst growth performance than other treatments. Significant differences (p<0.05) were detected on day 7, 30, 60, and 90 among treatment sheep. T1 showed the highest growth hormones compare to other treatments and T3 sheep revealed the highest reduction in growth hormone concentration. Despite the ADG and weight gain result for long-term and growth hormones, there were no significant differences on the body measurement during both terms including the body indexes. Overall, feeding sheep with the high level of B. decumbens showed inferior in the gas production and rumen fermentation, growth performance and digestibility as compared to the control group fed with P. purpureum with 0% of B. decumbens. The effects of both low and high saponin levels of B. decumbens on In Vitro study and growth performance on sheep from this study may contribute to future research of B. decumbens.